2018
DOI: 10.4274/mjima.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires' Disease

Abstract: REVIEW / DERLEME Legionnaires' disease is a severe form of pneumonia caused by Legionella species which are ubiquitous in both natural and man-made environments. It causes high morbidity and case fatality rates. The disease is acquired by aspiration of water or inhalation of aerosols containing the bacteria from environmental sources. Early diagnosis and appropriate treatment are important factors in determining the prognosis. Clinical and laboratory predictors will not reliably identify cases of Legionnaires'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Anyway, although this type of thermal disinfection can be regarded as an effective control method, it has been seen that the genus Legionella has shown adaptation to a wide range of temperatures. Laboratory studies, for example, have shown that it can survive for 80–120 min at 50 °C and 2 min at 60 °C [ 10 ]. In real settings, some species, including L. pneumophila , were found able to grow at temperatures above 50 °C, and to survive up to 63 °C [ 11 ].…”
Section: Factors Related To the Growth And Survival Of Legionellaementioning
confidence: 99%
“…Anyway, although this type of thermal disinfection can be regarded as an effective control method, it has been seen that the genus Legionella has shown adaptation to a wide range of temperatures. Laboratory studies, for example, have shown that it can survive for 80–120 min at 50 °C and 2 min at 60 °C [ 10 ]. In real settings, some species, including L. pneumophila , were found able to grow at temperatures above 50 °C, and to survive up to 63 °C [ 11 ].…”
Section: Factors Related To the Growth And Survival Of Legionellaementioning
confidence: 99%
“…Aerosols are solid or liquid particles suspended in air and can contain particles of any size 12 . The biofilm layers in the water and the amoeba and the cilia protozoa serve as both a food source and a shelter in adverse conditions and are survival surfaces for Legionella 13 . Studies show that 20 amoeba and two ciliated protozoa are hosts for Legionella.…”
Section: Introductionmentioning
confidence: 99%
“…LD is also a significant cause of hospital-acquired pneumonia with very high mortality rates (40–80%) especially in immunocompromised patients when left untreated (WHO, 2011). Even when it is timely diagnosed and the proper therapy is followed, the rates remain high (5–30% among immunocompromised patients and 10–15% in immunocompetent patients) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%